THE EFFECT OF LACTIC ACID AND ARTIFICIAL SALIVA SOLUTION IMMERSION TO THE RELEASE OF CALCIUM IONS ON BIOACTIVE RESIN - Dewi Puspitasari; Nurah Tajjalia; Diana Wibowo; Agung Satria Wardhana (Dentino : Jurnal Kedokteran Gigi, 2021)
Background: Bioactive resin can release calcium ions when contact with solution media, even in acid condition. In the oral cavity, pH may change into acid condition due to the metabolic results of Streptococcus mutans. The bacteria metabolize carbohydrates into organic acids, one of which is lactic acid. Purpose: Analyze the effect of lactic acid solution and artificial saliva on the number of the release of calcium ions of bioactive resin. Methods: Forty-two specimens (diameter 15 mm x thickness 1 mm; n= 7/group fabricated with Activa™ Bioactive Restorative (Pulpdent). The specimens that meet the criteria were divided into 6 groups. The specimen was immersed for 1 and 7 days in the incubator at 37oC. The number of calcium ion release is measured using titration method. Results: Two Way Anova test and Post Hoc Bonferonni test showed there were significant differences among all group for lactic acid 1 day (4.040 ± 0.360) µg, artificial saliva 1 day (0.640 ± 0.338) µg, distilled water 1 day (1.040 ± 0.504) µg, lactic acid 7 days (5.400 ± 0.312), artificial saliva 7 days (1.640 ± 0.215) µg, distilled water 7 days (3.520± 0.356 µg). Conclusion: There was an influence of lactic acid and artificial saliva on the number of calcium ion releases of bioactive resin. Immersion of bioactive resin in the lactic acid solution increase the calcium ion releases and artificial saliva decrease the calcium ion release compared to distilled water. Keywords: artificial saliva, bioactive resin, calcium ion release, lactic acid